RANCANG BANGUN MESIN PEMOTONG RUMPUT TENAGA SURYA UNTUK NAVIGASI - john ohoiwutun (LPPM Poltek ST Paul, 2015)
Utilization of conventional energy sources such as coal, fuel oil, natural gas and others on the one hand has a low operating cost, but on the other side of the barriers is the greater source of diminishing returns and, more importantly, the emergence of environmental pollution problems dangerous to human life. This study aims to formulate the kinematics and dynamics to determine the movement of Solar Power Mower. In this study, using solar power as an energy source to charge the battery which then runs the robot. Design and research was conducted in the Department of Mechanical Workshop Faculty of Engineering, University of Hasanuddin of Gowa. Control system used is a manual system using radio wave transmitter and receiver which in turn drive the robot in the direction intended. Experimental results showed that treatment with three variations of the speed of 6.63 m / s, 8.84 m / s and 15.89 m / sec then obtained the best results occur in grass cutting 15.89 sec and high-speed cutting grass 5 cm. Formulation of kinematics and dynamics for lawn mowers, there are 2 control input variables, x and y ̇ ̇ 3 to control the output variables x, y and θ so that there is one variable redudant. Keywords: mobile robots, lawn mower, solar power